2022
DOI: 10.1016/j.crviro.2022.100019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of broad anti-coronavirus chemical agents for repurposing against SARS-CoV-2 and variants of concern

Abstract: Endemic human coronaviruses (hCoVs) 229E and OC43 cause respiratory disease with recurrent infections, while severe acute respiratory syndrome (SARS)-CoV-2 spreads across the world with impact on health and societies. Here, we report an image-based multicycle infection procedure with α-coronavirus hCoV-229E-eGFP in an arrayed chemical library screen of 5440 clinical and preclinical compounds. Toxicity counter selection and challenge with the β-coronaviruses OC43 and SARS-CoV-2 in tissue culture and human airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 111 publications
(118 reference statements)
2
26
0
Order By: Relevance
“…The IMPDH inhibitors mycophenolic acid (MPA) and merimepodib have previously been shown to inhibit SARS-CoV-2 infection in VeroE6 cells (56-58). MPA also showed antiviral effect in lung organoids and in nasal and bronchial epithelial explants (59,60). Specifically, the compounds are reported to have antiviral efficacies of 45.67% and a SI of >147 for MPA and efficacy of 72.28% for merimepodib in VeroE6 cells ( Table 3 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The IMPDH inhibitors mycophenolic acid (MPA) and merimepodib have previously been shown to inhibit SARS-CoV-2 infection in VeroE6 cells (56-58). MPA also showed antiviral effect in lung organoids and in nasal and bronchial epithelial explants (59,60). Specifically, the compounds are reported to have antiviral efficacies of 45.67% and a SI of >147 for MPA and efficacy of 72.28% for merimepodib in VeroE6 cells ( Table 3 ).…”
Section: Resultsmentioning
confidence: 95%
“…1 SI, the compound concentration toxic to cells (CC50/EC50) 2 EC50, the compound concentration required to inhibit virus replication by 50% CC50, the compound concentration required to reduce the cell viability by 50% compared to uninfected control from NCATS or CoV-RDB resource The IMPDH inhibitors mycophenolic acid (MPA) and merimepodib have previously been shown to inhibit SARS-CoV-2 infection in VeroE6 cells (56)(57)(58). MPA also showed antiviral effect in lung organoids and in nasal and bronchial epithelial explants (59,60). Specifically, the compounds are reported to have antiviral efficacies of 45.67% and a SI of >147 for MPA and efficacy of 72.28% for merimepodib in VeroE6 cells (Table 3).…”
Section: Network-approach Identifies Context-specific Inhibitors Of V...mentioning
confidence: 99%
“…For example, H. L. Xiong and coworkers at Xiamen University (Xiamen, China) found MeBlu to have an IC 50 of 9 μM in a VSV-SARS-CoV-2-Sdel18 pseudovirus assay when tested as one of the 12 selected compounds of promising activity identified from the screening of 1403 FDA-approved drugs [ 40 ]. Finally, an image-based multicycle replication assay-based repurposing screening of a chemical library of 5440 compounds that are approved, in clinical trial or in preclinical development, by Murer, Greber, and coworkers at the University of Zurich (Zurich, Switzerland) identified MeBlu as one of two promising candidates (the other being mycophenolic acid) that have low micromolar activity against SARS-CoV-2 (1.4 μM) [ 41 ]. While Cagno et al reported a good therapeutic index for MeBlu in Vero E6 cell-based assay (TI = 46.1/0.11 = 420) [ 36 ], this study by Murer et al with Huh7 cells found it to be even lower (TI = 8.7/1.4 = 6.2) [ 41 ] than that obtained here with HEK293T cells (TI = 12–16).…”
Section: Discussionmentioning
confidence: 99%
“…The clone 120.03 is from a healthy donor and 105.03 has a mutation in CD48, but this gene is not expressed in fibroblasts [ 55 ]. A549 cells expressing the SARS-CoV-2 receptor angiotensin-converting enzyme 2 (A549-ACE2 cells) were used as described [ 56 ]. A549 RIG-I and A549 IFNAR2 knockout (KO) cells were generated from ATCC A549 cells by CRISPR/Cas9 technology using a lentivirus vector for a doxycycline-inducible expression of Cas9 and a U6-promoter-driven expression for the gRNA.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 “Wuhan” (TAR clone 3.3, München-1.1/2020/929) was obtained from Dr. Volker Thiel (University of Bern, Bern, Switzerland) [ 61 ]. SARS-CoV-2 experiments were conducted at BSL3 conditions (Institute of Pathology, University of Zürich, Zürich, Switzerland), as described [ 56 ].…”
Section: Methodsmentioning
confidence: 99%